Electoral Rules and Political Selection Theory and Evidence from a Field Experiment in Afghanistan - Beath, Andrew (World Bank E-Library Archive, 2015)
Voters commonly face a choice between competent candidates and those with policy preferences similar to their own. This paper explores how electoral rules, such as district magnitude, mediate this trade-off and affect the composition of representative bodies and policy outcomes. The paper shows formally that anticipation of bargaining over policy causes voters in elections with multiple single-member districts to prefer candidates with polarized policy positions over more competent candidates. Results from a unique field experiment in Afghanistan are consistent with these predictions. Specifically, representatives elected in elections with a single multi-member district are better educated and exhibit less extreme policy preferences